2016
DOI: 10.3390/md14020035
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-Atherosclerotic Properties of Astaxanthin

Abstract: Astaxanthin is a naturally occurring red carotenoid pigment classified as a xanthophyll, found in microalgae and seafood such as salmon, trout, and shrimp. This review focuses on astaxanthin as a bioactive compound and outlines the evidence associated with its potential role in the prevention of atherosclerosis. Astaxanthin has a unique molecular structure that is responsible for its powerful antioxidant activities by quenching singlet oxygen and scavenging free radicals. Astaxanthin has been reported to inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 88 publications
(92 reference statements)
1
120
0
9
Order By: Relevance
“…; Kishimoto et al . ). Accumulating evidence from available data over the yesteryears have unanimously suggested that astaxanthin is relatively safe to be incorporated into the feed of various animals and human subjects as a nutritional supplement or additive without any identifiable negative consequences.…”
Section: Safety Of Astaxanthinmentioning
confidence: 97%
See 1 more Smart Citation
“…; Kishimoto et al . ). Accumulating evidence from available data over the yesteryears have unanimously suggested that astaxanthin is relatively safe to be incorporated into the feed of various animals and human subjects as a nutritional supplement or additive without any identifiable negative consequences.…”
Section: Safety Of Astaxanthinmentioning
confidence: 97%
“…No observable serious side effects of astaxanthin have been recorded thus far in any of the published human clinical studies when administered to humans, and there is evidence of a suppression in biomarkers of inflammation and oxidative stress (Spiller & Dewell 2003;Kim & Chyun 2004;Iwabayashi et al 2009;Satoh et al 2009;Park et al 2010;Fassett & Coombes 2011;Yamashita 2015). A growing body of research suggests that dietary astaxanthin supplementation could exert protective actions against atherosclerotic cardiovascular disease (CVD) via its potential as a therapeutic agent to ameliorate endothelial inflammation, oxidative stress, neutrophil functions, flexibility of red blood cell membranes, lipid and glucose metabolism (Macedo et al 2010;Riccioni et al 2012;Kishimoto et al 2016). Accumulating evidence from available data over the yesteryears have unanimously suggested that astaxanthin is relatively safe to be incorporated into the feed of various animals and human subjects as a nutritional supplement or additive without any identifiable negative consequences.…”
Section: Safety Of Astaxanthinmentioning
confidence: 99%
“…In light of its multiple biological actions, the xanthophyll carotenoid astaxanthin has been proposed as a suitable preventive and therapeutic agent in cardiovascular disease (Kishimoto et al 2016). Astaxanthin exhibited lipid-lowering activity in laboratory mice supplemented diet with >0.03% of astaxanthin from H. pluvialis for 12 weeks, namely, lowering plasma TG concentrations.…”
Section: Astaxanthinmentioning
confidence: 99%
“…Sulforaphane was also shown to inhibit the expression of TNF-a-induced adhesion molecules in VSMCs [99]. Astaxanthin inhibits LDL oxidation and increases the high-density lipoprotein (HDL) cholesterol and adiponectin levels; astaxanthin could exert preventive actions against CVD via its potential ability to improve oxidative stress, inflammation, lipid metabolism and glucose metabolism [100].…”
Section: Anti-aopps Strategies and Atherosclerosismentioning
confidence: 99%